Progesterone Profiles During the Estrous Cycle and Pregnancy of Grazing Bali Cows Supplemented with Concentrate - Belli, HLL; Jelantik, IGN (ANIMAL PRODUCTION, 2009)
The influence of concentrate during estrous cycle and pregnancy on pattern of progesterone were studied. Seventeen calf-rearing cows were devided randomly into two groups, group A (N=9 were grazed on natural pasture as basal diet, whereas goup B (n=8) received additional 2.4 kg concentrate consists of 1.2 kg corn meal, 0.6 kg rice bran and 0.6 coconut cake. Animals from each group were closely observed for estrous characteristics i.e. estrus detection two times a day by two experienced technisians. Blood sample taken 3-times per week from jugular vein were used for assessing plasma progesterone concentrations using RIA procedure. Plasma progesterone concentrations were not influenced by concentrate supplementation neither during successive estrous cycles nor during pregnancy. The concentrations began to rise on day 4 of the cycle (1.9 ng/mL and 1.8 ng/mL) and increased to concentrations as high as 5.4 ng/mLÂ  and 5.1 ng/mL for supplemented and non-supplemented cows during the luteal phase (day 12) before returning to basal levels i.e. 0.1 ng/mL and 0.1 ng/mL, before ovulation. Following conception, plasma progesterone increased from 0,16 ng/mL and 0.21 ng/mL at estrus to 3.6 ng/mL and 2.73 ng/mL at week-1 and then rose to 5.09 and 4.57 ng/mL at week-2 for NS and S groups, respectively. Aftewards, progesterone continued to rise to 5,46 ng/mL and 5.17 ng/mL on week-3, and then reached 6.25 and 5.3 ng/mL for non-supplemented and supplemented cow, respectively. During 10 weeks pre-calving period, progesterone levels declined gradualli achieving levels 2.83 ng/mL and 2.87 ng/mL in the non-supplemented and supplemented groups, respectively, declined markedly 1 to 2 days prior to parturition and remained at these levels before reaching the basal level after parturition. (Animal Production 11(2): 79-87 (2009)Â Key Words: Bali cows, progesterone, estrous cycle, pregnancy